Ranking and rating halal-certified restaurants in Malaysia: an application of AHP - Azam, Md Siddique E; Ahmad, Anis Najiha; Jaiyeoba, Haruna Babatunde (Emerald Publishing Limited, 2024)
Purpose – The purpose of the study is to measure the performance level of halal compliance practices by the halal-certified restaurants in Malaysia and rank and rate them based on several dimensions of halal compliance. Design/methodology/approach – A total of 320 halal restaurants were surveyed. The absolute measurement approach of the analytic hierarchy process (AHP) was applied to rank and rate the restaurants. Finally, ANOVA and independent t-test were applied to assess if there is any significant difference in halal compliance performance between different groups of the respondents. Findings – The AHP application resulted in only 19 restaurants (5.94%) achieving an “Excellent” rating. A significant difference has been observed between different groups of the respondents regarding their halal compliance performance. Research limitations/implications – An onsite audit and ranking of all the restaurants in Malaysia were beyond the scope of the study. The research was able to rank only 320 restaurants across Malaysia. Practical implications – The findings and methodology of the study will provide policymakers with a clear roadmap for establishing a comprehensive rating system in the fields of the halal food industry to enhance the quality and integrity of the halal food management system. Originality/value – To the best of the authors’ knowledge, this is the first time an empirical approach, like AHP, has been used to determine how Malaysia’s halal-certified restaurants stack up against one another. Similar studies can be carried out in other sectors of the halal industry as well as in similar context.